Green synthesis of Cicer arietinum waste derived silver nanoparticle for antimicrobial and cytotoxicity properties. (January 2023) - Mouriya, Govindan Kothandaraman; Mohammed, Mas; Azmi, Alyza A.; Khairul, Wan M.; Karunakaran, Thiruventhan; Amirul, Al-Ashraf Abdullah; Ramakrishna, Seeram; Santhanam, Rameshkumar; Vigneswari, Sevakumaran
Abstract: Transforming inexpensive waste into useful product is gaining attention due to the economic and environmentally friendly approach. The disposal of agricultural waste generated is often a major problem faced by many countries. In this study, silver nanoparticles (AgNPs) are biosynthesised using black chickpea ( C. arietinum ) peels, an agro-industry waste as reducing and capping agent. The chemical components of C. arietinum aqueous peel extract was analysed using liquid chromatography with tandem mass spectrometry (LCMS/MS). The synthesised C. arietinum AgNPs, was characterised for their physicochemical properties as well as examined for antimicrobial, cytotoxic, and anticancer properties. The particle size distribution was in the size of 47.46 nm. Based on the FT-IR analysis, the functional groups present in the synthesized C. arietinum AgNPs, include alkyl halides (C–Cl), proteins (C–N), and nitro compounds (NO). The AgNPs demonstrated antimicrobial properties against common pathogenic Gram-negative and Gram-positive bacteria. Significant inhibitory zones are observed as follows Escherichia coli (14 ± 0.5 mm), Staphylococcus aureus (13 ± 1 mm), Pseudomonas aeruginosa (13 ± 0.5 mm), and Bacillus cereus (10 ± 0.5 mm). The cytotoxicity of C. arietinum AgNPs was assessed against 3T3-L1 fibroblast cell and MCF-7 cancerous cell lines. The AgNPs exhibited selective cytotoxic effect against cancer cells with the IC50 value 82.016 μg/mL and non-toxic effect in normal fibroblast cells. This study proves that C. arietinum peel AgNPs has good antimicrobial and anticancer properties and has potential to be developed for effectual medical application. Graphical abstract: Image 1 Highlights: Black chickpea husk waste to silver nanoparticles via biological synthesis. AgNPs have shown significant antimicrobial and anticancer properties. These AgNPs holds great potential as low-cost and environmental-friendly.